Penyimpangan Nilai-Nilai Etika Dalam Berbusana Adat Ke Pura Di Desa Penarungan Kecamatan Mengwi Kabupaten Badung - Arista Jaya, I Kadek; Perbowosari, Heny; Sedana Suci, I Gede (Jayapangus Press, 2021)
The development of global currents has an impact on various aspects of life, including community culture. One of them is in terms of clothing which is influenced by foreign cultures. This of course degrades ethical values ​​in the use of clothing, especially clothing used at social events or places of worship such as traditional clothing to temples. The influence of outside culture that is abused certainly causes deviations in ethical values ​​in the use of traditional clothing to the temple, one of the villages affected by the deviation is Penarungan Village. As a tourism destination, the people of Penarungan Village cannot turn a blind eye to outside culture, this causes deviations in ethical values ​​of traditional dress to the temple in Penarungan village. This research uses value theory, behaviorism, and social interaction. The approach used is ethnography. Informants were determined by purposive sampling. The research location chosen was Penarungan Village. Data collection techniques are by observation, interviews, and library techniques. The results of the study show that the forms of deviation from ethical values ​​in traditional attire to the temple in Penarungan Village include: (1) Deviations using kamen, (2) loose hair, (3) transparent and vulgar clothes, (4) T-shirts. the causes of deviations in values. Ethical factors in traditional kepura dress in Penarungan Village include (1) social media, (2) development of the times, (3) economic factors. The strategies of Hindu religious leaders in strengthening ethical values ​​in traditional attire to temples in Penungan Village (1) bring order to the people who violate them, (2) use uniform clothing.